Social inequality in youth violence: The role of heavy episodic drinking. (27th June 2017) - Norström, Thor; Rossow, Ingeborg; Pape, Hilde
Abstract: Introduction and Aims. Alcohol use is an important risk factor for violence, and violent behaviour is more prevalent in lower socioeconomic status (SES) groups. The aim of this study was to examine whether the SES difference in youth violence can be explained by differential exposure to—and/or differential vulnerability to—heavy episodic drinking (HED). In the latter case, effect modification by impulsivity could be assumed.Design and Methods. We analysed cross‐sectional data from a school survey of 15‐ to 17‐year‐olds in Norway ( n = 9853). We employed two measures of low‐SES group. Associations between SES, HED and violence were estimated by Poisson regressions, applying a residual centring procedure to test effect modification.Results. Violent behaviour frequency, HED frequency and impulsivity scores were all elevated in the low‐SES group. The SES difference in violent behaviour was significantly reduced when adjusting for HED. The stronger association between HED and violence in the low, compared with the medium‐SES/high‐SES group, was modified when accounting for impulsivity. Sensitivity analyses suggested robust findings.Discussion and Conclusions. The findings lend support to both the differential exposure hypothesis and to the differential vulnerability hypothesis as well as the hypothesis of an enhancing effect of impulsivity on the HED—violence association. The SES difference in youth violence can be accounted for by: (i) an elevated prevalence of HED in low‐SES groups; and (ii) a stronger than average link between HED and violence in low‐SES groups due to their higher than average impulsivity score. [Norström T, Rossow I, Pape H. Social inequality in youth violence: The role of heavy episodic drinking. Drug Alcohol Rev 2017;00:000‐000]